3D structure prediction of OCT 4, an important Reprogramming Factor of induced Pluripotent Stem Cells (iPSCs) - Chauhan, P.; Wal, N. (International Journal of Scientific Research in Biological Sciences, 2018)
Oct 4 is one of the transcription factors among six reprogramming factors (OCT4, SOX2, KLF4, C-MYC, NANOG, and LIN28) selected by Takahashi and Yamanaka to induce somatic cells into pluripotent stem cells (iPSCs).Stem cell research is used in treatment of a number of diseases including genetic disorders. Several questions regarding reprogramming factors of stem cells are remaining unanswerable due to limited experimental availability and ehilical issues. Proteomic analysis of OCT 4 is still remaining unpredicted as protein structure is not available in PDB. The aim of this study was prediction of the tertiary structure of OCT4 protein using homology modeling approach through MODELLER program. Quality and reliability assessments were performed on predicted model and found the model reliable.